2021
DOI: 10.47162/rjme.62.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-functionalized dressings for the treatment of third-degree skin burns – histopathological and immunohistochemical study

Abstract: Skin burns are one of the most common injuries associated with increased morbidity and mortality, especially in the children and the elderlies. Severe burns, especially, result in a systemic immune and inflammatory response, which may reflect in multiple organ insufficiency, and a fast and effective local restorative process is essential for functionality recovering, as well as for interrupting the generalized systemic response. We have aimed here to assess the effect of different wound dressings in what it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In contrast, the collagen fibers in the control group were arranged obliquely and loosely. Angiogenesis is one of the most researched processes in a burnt wound [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the collagen fibers in the control group were arranged obliquely and loosely. Angiogenesis is one of the most researched processes in a burnt wound [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that after skin injury, monocytes gather on the wound surface and differentiate into macrophages, which subsequently perform phagocytosis to remove damaged cells and tissues, promote angiogenesis, and skin re-epithelialization. They play a key role in the initiation and resolution of inflammatory responses in both acute and chronic injuries [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This action restores the functions of the epidermal permeability barrier by promoting the differentiation of keratinocytes and facilitating the de novo synthesis of ceramides [ 117 ]. EV treatment improved trauma recovery by epidermal stratification after burn injury [ 137 ] and enhanced epidermal re-epithelialization [ 98 ]. Interestingly, EVs reduced the proportion of epidermal stratification and ameliorated skin photodamage in a rat model of photoaged skin [ 119 ].…”
Section: Msc-derived Evs For Wound Repairmentioning
confidence: 99%
“…The collagenous fibers, fibroblasts, arteries, and nerves that are abundant in the dermis provide strength, nutrition, and sensation to the skin [ 4 , 136 ]. MSC-derived EVs enhance the amount of new dermis at the trauma surface [ 114 , 119 ] and promote granulation tissue maturation and epidermal basement membrane structuring in burn wounds [ 137 ]. This process also inhibits the formation of hyperplastic scars and keloids through the miR-192-5p/interleukin (IL)-17RA/Smad axis and promotes dermal regeneration [ 105 , 114 ].…”
Section: Msc-derived Evs For Wound Repairmentioning
confidence: 99%